2010
DOI: 10.1016/s0929-6646(10)60058-7
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy for a Patient With Chronic Mesenteric Ischemia

Abstract: Percutaneous transluminal angioplasty is now used widely in the revascularization of peripheral artery disease. We report the case of a 75-year-old woman with chronic mesenteric ischemia, who presented with postprandial abdominal pain, food fear, and weight loss for 6 months. Mesenteric angiography showed critical stenosis in the celiac trunk, and superior and inferior mesenteric arteries. Instead of surgical revascularization, balloon angioplasty and stenting was performed on the celiac trunk and superior mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Actualmente, existen múltiples estudios en los cuales se evalúan el tratamiento quirúrgico abierto y el endovascular 15,22,23,[27][28][29][30] . En un estudio en los Estados Unidos de 22.413 pacientes con isquemia mesentérica crónica sometidos a reperfusión, se encontró que con el tratamiento endovascular, la mediana de la estancia hospitalaria fue menor (5 Vs. 11 días; p<0,001) y, también, la morbilidad (20 Vs. 38 %; p<0,001); en el análisis multivariado, la mortalidad fue cinco veces mayor en el grupo de reperfusión abierta (odds ratio, OR=5,1) (IC 95% 3,1-8,4; p=0,001) (23).…”
Section: Discussionunclassified
“…Actualmente, existen múltiples estudios en los cuales se evalúan el tratamiento quirúrgico abierto y el endovascular 15,22,23,[27][28][29][30] . En un estudio en los Estados Unidos de 22.413 pacientes con isquemia mesentérica crónica sometidos a reperfusión, se encontró que con el tratamiento endovascular, la mediana de la estancia hospitalaria fue menor (5 Vs. 11 días; p<0,001) y, también, la morbilidad (20 Vs. 38 %; p<0,001); en el análisis multivariado, la mortalidad fue cinco veces mayor en el grupo de reperfusión abierta (odds ratio, OR=5,1) (IC 95% 3,1-8,4; p=0,001) (23).…”
Section: Discussionunclassified
“…Mortality rates in several articles vary from 0-17% after endovascular therapy. [5][6][7] Morbidity rate ranges between 19-54% 4 (Table 3). A cumulative analysis of Kougias et al in 2007 8,9 showed technical success of endovascular treatment in 91% of the cases, with a complication rate of 9%, and a 30-day mortality of 3%.…”
Section: Discussionmentioning
confidence: 99%